The Misconceptions about Electric Pressure Cookers - Nelly Nelson; Meghan Brunelli; Tara Jett (EDIS)
Pressure cookers became a popular kitchen appliance in the 1950s and were commonly used to can homegrown produce. Now pressure cookers are making a comeback and are helping families cook amazing meals in a fraction of the time. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department provides some basic information about pressure cookers and how best to use them. Written by Nelly Nelson, Meghan Brunelli, and Tara Jett. https://edis.ifas.ufl.edu/fs446